IITA wins development partner award! OYO STATE - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
IITA has received the Development Partner Award at the Oyo State Governor’s Dinner and Tourism Award held on July 24, in recognition of our unwavering commitment to environmental protection and healthy climate development in Oyo State. The award was received on behalf of IITA by Olukunle Olasupo, Field Supervisor, IITA Forest Center—a model of ecological preservation and sustainable tourism in the heart of Ibadan. This honor reflects our continued efforts in conserving biodiversity, advancing climate action, and safeguarding the IITA Forest Reserve, a vital green lung in Ibadan and a hub for eco-tourism and conservation education.